Zinc as an Essential Micronutrient and Its Positive Impact in Improving Body Immunity to Infection Through Nutritional Approach: A Literature Review - Permataputri, Chy’as Diuranil Astrid (Faculty of Medical - UPN Veteran Jawa Timur, 2024)
Background: Zinc is an essential mineral involved in various biological functions, including the regulation of the immune system. Zinc deficiency can lead to impaired immune function, increased susceptibility to infections, and delayed healing of diseases. Methods: We searched the Pubmed and Google Scholar databases using relevant keywords such as “zinc”, “zinc supplementation”, “essential micronutrients”,